Electromyographic activities of the jaw and facial muscles in subjects with different vertical skeletal patterns and breathing modes. (13th February 2023) - Zhao, Minyue; Han, Mengqi; Habumugisha, Janvier; Mohamed, Amin S.; Bu, Wenqing; Guo, Yucheng; Zou, Rui; Wang, Fei
Abstract: Background: Mouth breathing (MB) can affect morphological changes in the craniofacial structures, electromyography is widely used for quantitative analysis of muscle function. Objective: The aim was to evaluate the electromyographic (EMG) activities of the anterior temporalis (TA), masseter muscle (MM), orbicularis oris superior (OOS) and mentalis muscle (MT) in children with different vertical skeletal patterns and breathing modes during rest and various functional mandibular movements. Methods: BioEMG III was used to measure the variations in EMG activities of TA, MM, OOS, and MT in 185 subjects aged 6–12 years during continuous clenching, rest, maximal intercuspation, lips closed lightly and swallowing. Results: The results of logistic regression analysis showed that the model with vertical skeletal patterns as the dependent variable was ineffective ( p = .106), while the model with breathing modes as the dependent variable was effective ( p = .000). When considering both vertical skeletal patterns and breathing modes, the following significant differences were found. (1) In the normal‐angle group, the EMG ratio in OOS with lips closed lightly of MB was significantly higher than NB ( p = .005). (2) In the low‐angle group, EMG ratios in TA and MM during the swallowing of MB were significantly lower than NB ( p = .020, p = .040, respectively). (3) In the high‐angle group, EMG ratios of MB were significantly higher in MT during continuous clenching, rest, lips closed lightly and swallowing ( p = .038, p = .036, p = .005, p = .028, respectively), and OOS with lips closed lightly compared to NB ( p = .005). Conclusion: Breathing modes and vertical skeletal patterns interacted to alter maxillofacial EMG activities, with breathing modes having a greater effect. Abstract : Breathing modes and vertical skeletal patterns interacted to alter maxillofacial EMG activities, with breathing modes having a greater effect on the maxillofacial EMG.